2018
DOI: 10.1038/s41598-018-21261-9
|View full text |Cite
|
Sign up to set email alerts
|

Threshold driven contagion on weighted networks

Abstract: Weighted networks capture the structure of complex systems where interaction strength is meaningful. This information is essential to a large number of processes, such as threshold dynamics, where link weights reflect the amount of influence that neighbours have in determining a node's behaviour. Despite describing numerous cascading phenomena, such as neural firing or social contagion, the modelling of threshold dynamics on weighted networks has been largely overlooked. We fill this gap by studying a dynamica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 53 publications
0
54
0
Order By: Relevance
“…We solve for our model using the approximate master equation (AME) formalism [43,44]. Similar to earlier solutions [10,14,16], at time t, the density of infected nodes ρ and the average probability ν j that a j-type neighbor of a susceptible node is infected are governed by the system of coupled differential equations,ν…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We solve for our model using the approximate master equation (AME) formalism [43,44]. Similar to earlier solutions [10,14,16], at time t, the density of infected nodes ρ and the average probability ν j that a j-type neighbor of a susceptible node is infected are governed by the system of coupled differential equations,ν…”
Section: Resultsmentioning
confidence: 99%
“…This behavior is well captured by threshold models of social contagion on single-layer unweighted networks, which predict large-scale cascades of adoption in relatively sparse networks [8-10, 10, 11]. In empirical social networks, however, individuals can maintain hundreds of ties [5,12], with interaction strength varying across social contexts [13][14][15], yet still exhibit frequent system-wide cascades of social contagion [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…One obvious way to analyze such a more general environment is to rely on numerical simulations. Hurd and Gleeson [24], Hurd [25] and Unicomb et al [26], however, proposed alternative approximation methods to compute the solution of cascade dynamics. Hurd and Gleeson [24,25] consider a situation in which edge weights w are random variables, whose CDFs G kk 0 ðwÞ depend on the degrees of nodes in both sides of an edge k and k 0 .…”
Section: Heterogeneous Edge Weightsmentioning
confidence: 99%
“…They show that by imposing additional assumptions, one can obtain the analytical solutions for the mean cascade size. Unicomb et al [26] …”
Section: Heterogeneous Edge Weightsmentioning
confidence: 99%
“…Examples of an LTM type spread mechanisms and of the heterogeneity of the thresholds are provided through a number of controlled experiments [46][47][48] and by empirical data analysis [49][50][51][52][53]. Unicomb et al [38] studied the threshold model in weighted networks and found that the time of cascade emergence depends non-monotonically on weight heterogeneities. Watts and Dodds [39] showed through simulations of various types of spread mechanisms that the cascade size is governed not by superspreaders, but by a small critical set of nodes with low resistance to influence.…”
Section: Introductionmentioning
confidence: 99%